Immigrant Capital and Entrepreneurial Opportunities - Malavika Sundararajan; Binod Sundararajan (Entrepreneurial Business and Economics Review)
Objective: The main objective of this study is to define and operationalize the concept of immigrant capital, a key factor that differentiates immigrant from host country entrepreneurs in how they recognize and start new ventures. Research Design & Methods: A detailed analysis of contemporary immigrant entrepreneurship and opportunity recognition literature was carried out. Using grounded theory, we synthesized the outcomes from the analysis of eight Canadian and U.S. case studies of successful immigrant entrepreneurs with the key findings from the literature to define and develop a model of immigrant capital. Findings: Based on our grounded theory development process we show that the concept of immigrant capital as a distillate of human, cultural, economic and social capital that goes beyond expected opportunity recognition (OR) drivers like prior knowledge and prior experience to differentiate and enhance the immigrant entrepreneur's ability to recognize business opportunities compared to host country entrepreneurs. We found immigrant capital to be a consequence of being boundary spanners in host and home country networks. Implications & Recommendations: Understanding a unique resource like immigrant capital, will help immigrant as well as host country entrepreneurs further develop their opportunity recognition ability by bridging gaps and fulfilling the needs for both, immigrant and host country consumers. Contribution & Value Added: The main contribution is the theoretical development, identification and definition of the immigrant capital model and propositions that will articulate the factors that lead to the conceptualization and operationalization of immigrant capital. Furthermore, the immigrant capital model can serve host country entrepreneurs to develop cross-cultural networks and jump-start entrepreneurial activities in their home countries as well as learn how to expand their operations into global markets.